1963
DOI: 10.2465/ganko1941.50.118
|View full text |Cite
|
Sign up to set email alerts
|

Minor elements in pyrite and their effects on the cube-edge of pyrite

Abstract: Investigations concerning the concentration of minor ele ments (Co, Ni, Mn, As) in pyrites and cube-edge measurements were carried out on thirty-nine specimens taken from the Chichibu mine (26 samples), the Taishu mine (7 samples), and the Ashio mine (6 samples), by using X-ray fluorescent method as well as X-ray diffraction method. The results obtained are as follows;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1968
1968
1968
1968

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Therefore, it may be considered that selenium is concentrated in the pyrite ores of the high-temperature-type rather than in those of the lowtemperature-type; this conclusion agrees with Takimoto's results. 2,5) Krauskopf17) reported that mercury in vein fluid was transported as mercuric chloride or as free mercury and free sulfur in a high-temperature gas phase. In both case, merucry should be concentrated in the low-temperature-type ores.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it may be considered that selenium is concentrated in the pyrite ores of the high-temperature-type rather than in those of the lowtemperature-type; this conclusion agrees with Takimoto's results. 2,5) Krauskopf17) reported that mercury in vein fluid was transported as mercuric chloride or as free mercury and free sulfur in a high-temperature gas phase. In both case, merucry should be concentrated in the low-temperature-type ores.…”
Section: Discussionmentioning
confidence: 99%
“…Samples that are heterogeneous or have unknown absorption and enhancement effects require special treatment. In general, heterogeneity can be removed by fusion to form a glass with a In cement materials (8-10, 87, 184, 348, 370, 371, 373, 399, 413) In metals (103,315,317,318) In minerals and ores (14,77,257,288) In miscellaneous materials (22,153,184,198,248,317,318,343,388,397,413,420) Antimony (65,67,105,163,322,326,330,341,347,355,356,397) Arsenic (86,105,138,162,198,222,248,249,293,SOI,387,397,418) Barium (17,65,…”
mentioning
confidence: 99%